An evaluation of functional outcome following minimally invasive plate osteosynthesis in fractures of the distal tibia - Subash, Yeshwanth; S., Prabhu Manickam; R., Ravikrishna; S., Priyadarshini; Naidu, Gunalan K. (International Journal of Research in Orthopaedics, 2017)
Background: Management of fractures of the distal tibia remains a challenging proposition due to the fact that the major part of the bone is in a subcutaneous location and the blood supply is quite precarious. Conventional forms of osteosynthesis are associated with high rates of infection and nonunion. Due to extensive soft tissue stripping, the vascularity is compromised and often results in poor wound healing and tends to compromise fracture healing as well. Closed reduction with minimally invasive plate osteosynthesis (MIPO) addresses these issues and has emerged as a viable treatment option with minimal complications. The aim of this study was to assess the functional outcome MIPO using locking compression plates (LCP). Methods: 32 patients with distal tibial fractures treated by MIPO technique with LCP fixation were studied from January 2012 to January 2014 and were followed up for a period of 2 years. Results: All the fractures in our series united well at the end of 6 months with mean time to radiological evidence of callus formation at 10 weeks and the mean time to fracture union was 20 weeks. There were 2 cases with varus angulation in our series and no cases with implant failure. There were 3 patients with superficial skin infections and no cases of deep infection. Conclusions: We conclude that MIPO with LCP is an effective treatment option for distal tibial fractures avoiding all the complications associated with other forms of internal fixation. We strongly recommend its usage in these types of complex injuries.